Production of high melting fraction of palm oil - Кузнецова, Лариса Николаевна; Папченко, Виктория Юрьевна; Демидов, Игорь Николаевич (Eastern-European Journal of Enterprise Technologies, 2012)
In Ukraine, there is a problem of production of hard fats with structure mechanical and physicochemical characteristics necessary for fat products industry. Besides, the scientific bases of tropical oils fractionating applying the solvent do not exist. That is why, the possibility of ethanol applying in technology of vegetable oil fractionating, in particular palm oil, is a topical problem of today. Hence, the main target of the research is to determine the conditions of production of high melting fraction of palm oil by fractional crystallization from ethanol solution. Different conditions of experiment were applied: temperature variation, crystallization duration, cooling rate. The product was obtained and its analysis shows that the high melting fraction of palm oil corresponds to the palm stearin according to the physiochemical characteristics.